On international household survey data availability for assessing pre-pandemic monetary and multidimensional poverty in developing countries. Issue 1 (31st December 2022) - Alkire, Sabina; Robson, Matthew
ABSTRACT: Data availability plays a crucial role in the fight against poverty. Yet, it lags behind the data available on most other economic phenomena. This paper catalogs and reviews existing data availability for low- and middle-income countries with a view to break the cycle of outdated poverty data and strengthen statistical systems – while drawing readers' attention to existing information and experiences. Countries that generate and analyze frequent and accurate poverty data are identified to show what is possible and to better document what is already available. Results show that data for both monetary and multidimensional poverty dramatically increased since 1980. Sixty countries already produce annual updates to key statistics, and some have continuous household surveys with cost-cutting synergies. International agencies have explored short surveys for comparable data but the success and uptake of these have not followed expected patterns. Certain regions have agreed on harmonized variable definitions across countries, and new technologies reduce lags between data collection and analysis. These existing resources and experiences can inform much-needed efforts to expand data availability.